CALLIDIOPINI BEETLES (COLEOPTERA, CERAMBYCIDAE) IN THE COLLECTION OF MUSEUM ZOOLOGICUM BOGORIENSE, INDONESIA. PART II, GENITALIA AND TAXONOMY OF THE GENUS TETHIONEA PASCOE - Yaheita Yokoi; Hiroshi Makihara; Woro A. Noerdjito (Treubia, 2021)
Species of Tethionea Pascoe, 1869, Callidiopini, in the collection of Museum of Zoologicum Bogoriense are reviewed. Two new species of the genus are described, T. peggieae sp. nov. and T. oculata sp. nov., both from Papua Province, Indonesia. In addition, T. unicolor Pascoe, T. strumosa Pascoe and T. tridentata Pascoe are redescribed. Their male genitalia are documented and illustrated in detail. In particular, the ejaculatory duct complexes of endophalli are carefully observed, as well as 8th sternites and tergites. For T. oculata sp. nov., the female genitalia are described. Morphological and taxonomical aspects of these species are discussed.